Intervenção fisioterapêutica com o EPI-NO®: efeitos sobre a extensibilidade e a força da musculatura do assoalho pélvico de primigestas. - Freitas, Síssi Sisconeto de (2018)
Introduction The perineum preparation techniques for childbirth have been sought with the aim of reducing the incidence of lacerations during the expulsive phase of labor. However, no studies were found to investigate the effects of perineal massage and EPI-NO® techniques on pelvic floor muscle (PFM) variables. Objective To evaluate the effect of physiotherapeutic interventions with perineal massage and EPINO ® on the extensibility and strength of MAP. Method Randomized controlled clinical trial; 20 primigravidae were divided into perineal massage group (PMG) and EPI-NO group (ENG). The groups performed eight sessions, two weekly. The PMG underwent a perineal massage protocol for 10 minutes and the ENG performed the intervention for 15 minutes, in which the flask was inflated slowly and gradually, according to the participant's tolerance. The strength was assessed by vaginal manometry and the extensibility of the PFM through the largest circumference of the EPI-NO® before, after four and eight sessions. For comparison of the groups in relation to the variables extensibility and muscular strength, in their three evaluations, the analysis of variance was performed, with covariance correction considering the pre-intervention measure as covariate, with significance level of 5%. Results The groups showed an increase in PFM extensibility when compared to the evaluations before and after 4 and 8 sessions (p <0.001); there was no difference between groups. Regarding muscle strength, no statistical differences were observed between evaluations or between groups. Conclusion Perineal massage and physiotherapeutic intervention with EPI-NO® increase extensibility and do not alter the strength of PFM.